An Fe simulation study of new friction materials from natural fibres on automotive brake pads - Sheng K.K.; Isa M.R. (American Institute of Physics Inc., 2024)
Brake pad is very important nowadays. The performance of vehicle is getting better and better so the braking system also needs to be improved. The usage of asbestos material in manufacturing brake pad is found to be harmful and hazardous to human the environment. The brake dust that produced from the brake pad can cause several cancer to human especially lung cancer. Some research papers are investigating on natural fibres to replace harmful asbestos material. Modern simulation software is developed to simulate the properties of material. This study focuses on the mechanical simulation and thermal simulation of the selected natural fibres which are palm kernel fibre (PKF), Kevlar and wood. For the design of the brake pad, it is referring to the Perodua Myvi 2018 edition. The 3D model is design by using Autodesk Inventor and imported to Ansys FE simulation software for the simulation part to determine mechanical properties and thermal properties of the materials. The palm kernel fibre (PKF) is found to be the most suitable material to replace the asbestos material among the other natural fibres. 2023 Author(s).